Pengaruh Evaluasi Proses Pembelajaran Dan Locus Of Control Terhadap Motivasi Belajar Siswa Di MAN 1 Padang - Yessy Marzona; Detman; Hendang Mayora (Kilau Publishing, 2025)
This study aims to determine: (1) the effect of learning process evaluation on students’ learning motivation, (2) the effect of locus of control (LOC) on students’ learning motivation, and (3) the effect of learning process evaluation and locus of control on students’ learning motivation. This research uses a quantitative approach with a population of 66 students at MAN 1 Padang. The sampling technique applied was total sampling, involving the entire population as the research sample. Data were collected using questionnaires and analyzed through Multiple Linear Regression with the help of SPSS Version 25. Hypotheses were tested using t-test and F-test. The results show: (1) learning process evaluation has a positive and significant effect on students’ learning motivation with t-count 2.252 > t-table 1.998 and a significance value of 0.028 < 0.05; (2) locus of control positively and significantly affects learning motivation with t-count 3.193 > t-table 1.998 and significance 0.002 < 0.05; (3) learning process evaluation and locus of control together significantly influence students’ learning motivation, indicated by F-count 10.697 > F-table 3.143 with a significance level of 0.000 < 0.05. These findings suggest that both variables play an important role in enhancing student motivation.